Model Partisipatif Penyusunan Buku Persyaratan sebagai Prasyarat Perlindungan Hukum Indikasi Geografis - Yeti Sumiyati; Tatty AR (Jurnal Hukum IUS QUIA IUSTUM, 2015)
The book term of Geographical Indication is a prerequisite for protecting Pandanwangi and Cianjur rice as Geographical Indication products since its registration requirements must be equipped with Geographical Indications book which provides us with a comprehensive and detailed description of the quality, reputation, and distinctive character of the product. Thus, it is highly suggested that the applicant institution represents the stakeholders of Pandanwangi and Cianjur rice have great competence and well expertise to its formulation in accordance with the applicable rules. On this basis, the research problems in this study are formulated as follows, first, are there any obstacles found in the compilation of the Book Term of Geographical Indications of Pandanwangi and Cianjur Rice? Second, how is the Participatory Model in compiling the Book Term of Geographical Indications? The method used in this study is a socio-legal research based on the approach of legal science and social sciences. The study concluded that, first, the constraints in the preparation of the Book Term of IG of Cianjur and Pandanwangi Rice include technical constraints, the legal culture of the society, and the lack of understanding of the benefits of IG protection. Second, a participatory model to guide the preparation of the Terms of IG of Cianjur and Pandanwangi Rice is applied through active cooperation between the Government, AP3C, and Universities.